2009
DOI: 10.1093/mp/ssn092
|View full text |Cite
|
Sign up to set email alerts
|

ABA-Mediated Inhibition of Germination Is Related to the Inhibition of Genes Encoding Cell-Wall Biosynthetic and Architecture: Modifying Enzymes and Structural Proteins in Medicago truncatula Embryo Axis

Abstract: Radicle emergence and reserves mobilization are two distinct programmes that are thought to control germination. Both programs are influenced by abscissic acid (ABA) but how this hormone controls seed germination is still poorly known. Phenotypic and microscopic observations of the embryo axis of Medicago truncatula during germination in mitotic inhibition condition triggered by 10 microM oryzalin showed that cell division was not required to allow radicle emergence. A suppressive subtractive hybridization sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 28 publications
6
78
0
1
Order By: Relevance
“…described cell wall alterations found in the tomato ABAdeficient sitiens mutant (Asselbergh et al, 2007) and with the hypothesized modulation of cell wall architecture by ABA signaling (Gimeno-Gilles et al, 2009). The relevance of the cell wall in directly mediating the resistance of Arabidopsis to different pathogens, including PcBMM, has been reported previously (Hernández-Blanco et al, 2007;Denoux et al, 2008;Sánchez-Rodríguez et al, 2009;Ramírez et al, 2011;Delgado-Cerezo et al, 2012).…”
Section: Discussionmentioning
confidence: 70%
“…described cell wall alterations found in the tomato ABAdeficient sitiens mutant (Asselbergh et al, 2007) and with the hypothesized modulation of cell wall architecture by ABA signaling (Gimeno-Gilles et al, 2009). The relevance of the cell wall in directly mediating the resistance of Arabidopsis to different pathogens, including PcBMM, has been reported previously (Hernández-Blanco et al, 2007;Denoux et al, 2008;Sánchez-Rodríguez et al, 2009;Ramírez et al, 2011;Delgado-Cerezo et al, 2012).…”
Section: Discussionmentioning
confidence: 70%
“…36 In embryo axes of non-dormant Medicago truncatula seeds germinating on water, the expression of genes involved in cell wall biosynthesis: xyloglucan endotransglucosylase (XET), cellulose synthase, arabinogalactan protein, two extensins and PPRD (protein with proline-rich domain) increased throughout germination. 37 More importantly, genes known to play a key role in cell-wall loosening and expansion, such as expansins, 1-3 glucanase and XET, were significantly expressed in the embryos as early as 5 or 15 h of imbibition, namely before germination completion and radicle extension. 37 It has been proposed that the endocytic delivery of cell wall pectins represents a ready-to-use reservoir of building blocks for rapid cell wall formation during cytokinesis 38 or cell expansion 39 and emerges to be critical for the polarity of pollen tubes.…”
Section: Resultsmentioning
confidence: 97%
“…37 More importantly, genes known to play a key role in cell-wall loosening and expansion, such as expansins, 1-3 glucanase and XET, were significantly expressed in the embryos as early as 5 or 15 h of imbibition, namely before germination completion and radicle extension. 37 It has been proposed that the endocytic delivery of cell wall pectins represents a ready-to-use reservoir of building blocks for rapid cell wall formation during cytokinesis 38 or cell expansion 39 and emerges to be critical for the polarity of pollen tubes. 40 So, the internalized RG-II observed here could operate as an intracellular pectin reservoir for the rapid cell expansion that proceeds upon imbibition.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, our observations raise an interesting possibility that ABA hypersensitivity of the AtMYB52 OX lines may be associated with changes in cell wall architecture. It has been reported that ABA inhibits seed germination by inhibiting cell-wall loosening and expansion (Gimeno-Gilles et al, 2009). On the other hand, cell wall arabinan is essential for guard cell function (Jones et al, 2003; and seedling growth (Gomez et al, 2009).…”
Section: Discussionmentioning
confidence: 99%